Penerapan Abdominal Stretching Exercise Untuk Mengurangi Dismenore Pada Mahasiswi DIII Keperawatan Universitas ‘Aisyiyah Surakarta - Khoirunnisa Nur Istiqomah; Erika Dewi Noorratri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Dysmenorrhea is still experienced by many women, menstrual pain appears for several days during menstruation. Dysmenorrhea or menstrual pain can have an impact on teenagers' daily activities. The prevalence of dysmenorrhea in Surakarta is 89.8%. Efforts to reduce dysmenorrhea can be done in two ways, namely pharmacological and non-pharmacological. One non-pharmacological therapy that can be done is abdominal stretching exercise. Objective: To describe the results of applying the Abdominal Stretching Exercise to reduce dysmenorrhea pain in DIII Nursing students at 'Aisyiyah University, Surakarta. Method: This application uses the case study method. This method focuses more on the actions or behavior produced, in this method the variable measured is the level of pain in adolescents with dysmenorrhea who have been given intervention for 3 days. Results: After carrying out the Abdominal Stretching Exercise on two respondents who experienced dysmenorrhea for three consecutive days, it showed a change in pain level, Ms. K's pain scale decreased by 2 and Ms. N's pain scale decreased by 3. Conclusion: The application of Abdominal Stretching Exercise can reduce the level of dysmenorrhea pain in DIII Nursing students at 'Aisyiyah University, Surakarta.